Dynamic Batch Mode Active Learning via L1 Regularization - Chakraborty, Shayok; Balasubramanian, Vineeth; Panchanathan, Sethuraman (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
We propose a method for dynamic batch mode active learning where the batch size and selection criteria are integrated into a single formulation.